Analisis kandungan logam Pb dan NO2 udara ambien Kampus UIN Jakarta - Nita Rosita (Faculty of Mathtmatics and Natural Sciences, 2026)
A study has been conducted on the analysis of heavy metals Pb and NO2 in ambient air at the UIN Jakarta campus. The purpose of the study was to determine the content of heavy metals Pb and NO2 in ambient air at the UIN Jakarta campus and then compared with air quality standards. Ambient air quality is an important factor in creating a healthy and sustainable campus environment. Measurements were carried out at strategic locations using methods according to the Indonesian National Standard (SNI), namely the wet ashing method for measuring Pb metals and the Griess Saltzman method for measuring NO2 in the air. Sample analysis used an atomic absorption spectrophotometer (AAS) and UV-Visible spectrophotometer. Measurements were taken for 1 hour in the morning. Nine air sample locations were taken from the UIN Jakarta campus. Based on the analysis results, the average Pb content was <0.0058-0.048 µg/Nm3 and the NO2 concentration in the air ranged from 0.04-1.32 µg/Nm³. The study results showed that the Pb and NO2 levels in ambient air at the UIN Jakarta campus were still below established quality standards. These results provide a general overview of the relatively good air quality at the UIN Jakarta campus and the importance of strengthening the Green Campus program.